2022
DOI: 10.3390/nu14071388
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Leptin Resistance in the Regulation of the Type I Interferon Early Response and the Increased Risk for Severe COVID-19

Abstract: Obesity, and obesity-associated conditions such as hypertension, chronic kidney disease, type 2 diabetes, and cardiovascular disease, are important risk factors for severe Coronavirus disease-2019 (COVID-19). The common denominator is metaflammation, a portmanteau of metabolism and inflammation, which is characterized by chronically elevated levels of leptin and pro-inflammatory cytokines. These induce the “Suppressor Of Cytokine Signaling 1 and 3” (SOCS1/3), which deactivates the leptin receptor and also othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 278 publications
(446 reference statements)
2
20
0
1
Order By: Relevance
“…Leptin is the link between metabolic and immunity responses involving T-cell activation upon an acute respiratory viral infection, including SARS-CoV-2. In obesity, there is a large dysregulation of endocrine and inflammatory events leading to an inadequate immune response to acute SARS-CoV-2 infection [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is the link between metabolic and immunity responses involving T-cell activation upon an acute respiratory viral infection, including SARS-CoV-2. In obesity, there is a large dysregulation of endocrine and inflammatory events leading to an inadequate immune response to acute SARS-CoV-2 infection [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is considered as a potential marker of obesity and its comorbidities—in particular, type 2 diabetes and CVD—due to its angiogenic and atherogenic effects [ 38 ]. Several studies have shown that leptin levels are positively correlated with BMI, waist circumference, hip circumference, and insulin resistance parameters [ 39 , 40 ]. It has been shown that leptin level increases not only with increasing BMI, but also depends on gender; in particular, women had significantly higher levels of leptin than men [ 41 ].…”
Section: Pro-inflammatory Adipokines In Obesity and Its Complicationsmentioning
confidence: 99%
“…Вакцинация пациентов с МС не выступила фактором, блокирующим повышение в крови уровня лептина в посковидном периоде с сохранением более высоких показателей у 78% через 12 месяцев, данная тенденция совпадала в обеих группах лиц с МС, но отсутствовала в группе здоровых вне зависимости от вакцинации. В аспекте иммунного ответа и поддержания хронического воспаления лептин является провоспалительным фактором и его повышение -проявление «лептиновой резистентности», отменяющее его положительные патогенетические эффекты и усиливающее метавоспалительные реакции [6]. При этом у больных с МС без вакцинации рост содержания лептина в сыворотке крови происходил на фоне снижения адипонектина, что усиливало дисбаланс отношения лептин/адипонектин и ассоциировано, по данным литературы, с вторичным повреждением эндотелия [2,10], прогрессированием атеросклероза (по собственным данным адипонектин -независимый фактор роста ЛПНП в анализируемой модели), снижением толерантности к глюкозе и др.…”
Section: российский иммунологический журналunclassified